SAT0371 The Impact of Trabecular and Cortical Alterations in Patients with Bone Marrow Edema and Arthralgia of the Lower Limbs. (23rd January 2014) - Resch, H.; Zendeli, A.; Kocijan, R.; Fischer, L.; Suess, D.; Haschka, J.; Muschitz, C.
Abstract : Background: Bone marrow edema (BME) is a localised painful bone lesion which is diagnosed by MRI and a frequent cause for severe pain in the joints of the lower limbs and. Ischemia, local osteoporosis and bone bruise/stress fractures are possible pathophysiological pathways. Besides these pathways BME also appear reactively within the inflammatory form of rheumatologic diseases as it is associated with future development of bone erosion. Only few data are available on bone micro structure of cortical and trabecular sites measured by high-resolution peripheral quantitative computed tomography (HR-pQCT) and serum bone turnover markers (BTM). The aim of this cross-sectional pilot study was to investigate bone mineral density (BMD) measured by DXA, bone micro structure and serum BTM values in patients presenting with arthralgia and BME at the lower limbs compared to age matched healthy controls (HC). Methods: We compared 14 patients (mean age 43.7 ± 19.2 yr) with atraumatic BME of lower limb (2 femoral head, 7 proximal tibia, 5 ankle) to 35 age matched healthy controls (HC). All subjects had DXA (GE Lunar iDXA) of spine and hip, a HR-pQCT (Scanco Medical) examination of distal radius and tibia including microarchitectural parameters. The volume of interest was separated into a trabecular and a cortical region. The periosteal and endosteal boundaries were defined using an automated contouring. The region between the two contours was considered the cortical compartment volume for measuring cortical porosity. Further serum examinations of BSR, CRP and of intact amino terminal propeptide of type I procollagen (PINP), type 1 collagen cross-linked C-telopeptide (CTX), 25-OH vitamin D3, intact parathyroid hormone (iPTH) were measured. Results: Areal BMD/BTM: BMD values measured by DXA as well as bone turnover marker (BTM), BSR and CRP were not statistically different between the groups. Mean BMD was in osteopenic range. HR-pQCT measurements-tibia: BME patients compared to HC had increased total bone area (TotalArea) (773.88 ± 238 vs 659.19 ± 113 mm², p < 0.05) and increased trabecular area (TrabArea) (689.89 ± 238.25 vs 555.74 ± 109.05 mm², p < 0.01), but a lower density of the compacta (Dcomp) (809.19 ± 65.78 vs 870.64 ± 74.49 mgHA/ccm, p < 0.01) and diminished average bone density (D100) (245.25±46.50 vs 286.98 ± 64.38 mgHA/ccm, p < 0.05) at the tibia compared to HC. Intracortical porosity (Ct.Po) at the tibia of patients with BME was significantly higher (8 ± 1.4 vs 5 ± 0.3 %, p < 0.05) and cortical thickness (Ct.th) (0.88 ± 0.24 vs 1.09 ± 0.31 mm, p < 0.05) was reduced. Trabecular thickness (Tb.th) (0.07 ± 0.01 vs 0.08 ± 0.01 mm, p < 0.05) was significantly decreased, whereas the number of trabeculae (Tb.N) did not differ from HC (1.83 ± 0.29 vs 1.74 ± 0.29 I/mm, p = 0.19). Conclusions: Our data strongly suggest that altered structural properties at both, cortical and trabecular compartments contribute to the susceptibility of BME. An increased bone area is in contrast to reduced bone density, and an enhanced cortical porosity seems to be combined with reduced cortical and trabecular thickness. This structural impairment might be responsible for the development of atraumatic BME and our findings contribute to the understanding and to the treatment of this localised bone lesion. Disclosure of Interest: None Declared